Pengaruh Latihan Shooting Menggunakan Punggung Kaki dan Kaki Bagian Dalam Terhadap Akurasi Menendang Penalti - Sukmana, Ragil; Saptani, Entan; Ahmad Fauzi, Rizal (Jurnal Porkes, 2024)
The problem of this research is the lack of mastery of basic soccer techniques, namely penalty shooting. This study aims to assess the accuracy of kicking penalties on extracurricular soccer members of SDN Sukatali. The method used in this study is a qusy experiment with a nonequivalent pretest and posttest control group design and the sample used is all members of extracurricular soccer by means of total sampling of 20 students. From the results of the calculation of the paired sample test T test in the shooting group of the instep and inner foot, the sig = 0.00 is obtained, which means it is smaller than 0.05, thus Ho is rejected and Ha is accepted. Based on the results of descriptive analysis, the average gain score of penalty kicking accuracy in the back of the foot group = 0.75 and in the inner foot group = 0.67. This means that both are quite effective for increasing the accuracy of kicking penalties in the soccer extracurricular of SDN Sukatali, but the average shooting of the instep is higher than shooting the inside leg.